P1831 Predictors and clinical consequences of silent ischaemic brain lesions following transcatheter aortic valve implantation. (17th January 2020) - Nagy, A I; Bartykowszki, A I; Varga, A I; Suhai, F; Apor, A A; Szilveszter, B; Kolozsvary, M; Karady, J; Panajotu, A A; Jermendy, A; Molnar, L; Simon, J; et al.
Abstract: Funding Acknowledgements: This study was supported by the János Bolyai Scholarship of the Hungarian Academy of Sciences Background: A number of studies aimed to identify the predictors of periprocedural cerebral embolizations related to transcatheter aortic valve implantation (TAVI). Much less investigated is the prevalence and determinants of subacute ischaemic brain lesions that develop following TAVI. Purpose: We sought to identify predictors of subacute clinically silent ischaemic brain lesions in patients following TAVI. Methods: Patients were included from the Rule out Transcatheter Aortic Valve Thrombosis with Post Implantation Computed Tomography (RETORIC) prospective trial. Echocardiography and brain MRI were performed after TAVI procedure, before hospital discharge. Cardiac CT was performed 6 months later to identify subclinical leaflet thrombosis (HALT), as well as repeat brain MRI, to identify any silent ischaemic lesions that appeared since the intervention. The cognitive trajectory of patients was assessed using the Addenbrookes cognitive test (ACE), performed shortly after TAVI and at 6-month follow-up (FU). All-cause mortality data was retrieved from the National Mortality Database. Results: 79 consecutive patients were included in the present analysis. 28% had known history of atrial fibrillation (AF). 33% of the cohort was treated with oral anticoagulant, of these 56% with single and 25% with dual antiplatelet therapy (DAPT). The mean CHA2DS2VASC score was 4. From discharge to the 6-month FU, 20 patients (25%) developed new silent ischaemic brain lesions on MRI. Clinically manifest stroke did not occur. On the 6-month CT, HALT was identified in 6 patients (8%). Clinical and imaging parameters, including age, body mass index, hypertension, dyslipidaemia, diabetes, smoking, statin-, OAC- and DAPT therapy, history of AF, history of stroke, echocardiographic metrics of left ventricular (ejection fraction, stroke volume index) and atrial (left atrial strain) function as well as HALT were analysed for association with ischaemic brain lesions. Of the above, only HALT showed significant association (OR:6, 58; p = 0.04) with silent brain embolizations. The cognitive trajectory from discharge till 6-month FU did not differ between patients with or without ischaemic focuses (ΔACEscore: 1.0 vs. 0.1; p = NS). Over a median FU of 553 (IQR 453 – 665) days, 8 patients died; 2 with and 6 without ischaemic lesions. Kaplan-Meyer analysis showed no difference in outcome between the two groups (p = 0.68) Conclusion: Subclinical leaflet thrombosis was identified as a significant predictor of subacute silent ischaemic brain lesions after TAVI. These lesions did not affect the overall cognitive performance or outcome of the patients.